Ihsan as a Core Principle of Filial Piety: A Comparative Thematic Exegesis of Al-Misbah and Al-Munir - Sabilatul Jannah; Ahmad Nurrohim; Sondos Jehad Shnewra (Solo International Collaboration and Publication of Social Sciences and Humanities, 2026)
Objective: This study aims to examine the meaning and relevance of the teachings of birrul walidain (filial piety to one's parents) in modern life through a comparative analysis of two contemporary thematic interpretations: Tafsir Al-Misbah by Quraish Shihab and Tafsir Al-Munir by Wahbah Az-Zuhaili. Theoretical framework: This research is based on the theoretical framework of Islamic ethics and the approach of thematic interpretation (maudhu'i), taking into account the normative and contextual dimensions of the verses of the Qur'an related to birrul walidain. Islamic morality theory is also used as a foundation in understanding the formation of individual and societal morals. Literature review: The literature review includes literature on contemporary thematic interpretations, the values of birrul walidain in the Qur'an, and socio-cultural dynamics related to changes in family values and moral challenges in the modern era. The literature also highlights the difference in approach between Quraish Shihab and Wahbah Az-Zuhaili in interpreting Islamic values. Methods: This study uses a qualitative method with a literature study approach. Primary data sources were obtained from two main tafsir works, namely Tafsir Al-Misbah and Tafsir Al-Munir, while secondary data came from relevant supporting literature. Results: The results of the study show that both interpretations affirm birrul walidain as a form of obedience to Allah and the moral foundation of life. Tafsir Al-Misbah emphasizes the social and psychological aspects contextually, while Tafsir Al-Munir emphasizes the normative and legal aspects of Sharia. Both agreed that birrul walidain includes respect, emotional support, financial assistance, and maintaining parental honor. Implications: These findings enrich the understanding of the relevance of the value of birrul walidain in the modern era and show the importance of an adaptive approach in applying the teachings of the Qur'an in the contemporary social context. This research also contributes to the development of thematic interpretations that are responsive to the dynamics of society. Novelty: This research offers a new contribution by comparatively analyzing two contemporary interpretations from the perspective of applying the value of birrul walidain in the modern context. This approach has not been widely used in the study of thematic interpretations that connect traditional values with contemporary reality.